Optimisation of microwave vacuum pyrolysis conversion of palm oil empty fruit bunches into biochar and bio-oil - Wilfrid , Ze; Balike, Musongo; Richard , Domga; Gilbert , Obarley Ndip; Jean Bosco, Tchatchueng (International Journal of Advanced Chemistry, 2024)
The optimization of the production of Bio-oil and Biochar, from palm oil empty fruit bunches (POEFB) usually thrown as waste, was achieved using microwave vacuum pyrolysis, with expectations of it being a novel source of energy. Moreover, the demand for energy resources is perpetually increasing, due to the rapid increase in population and industrial developments. Surface response methodology via the central composite design was used to investigate the significance of microwave power (w), pyrolysis time (min) and absorbent / biomass ratio (g/g) on the yields in bio-oil and Biochar from POEFB. The optimal yield in bio-oil was 35.05 wt. %, obtained at 14.4 minutes, a ratio of 1: 24 and a power of 382 W and optimum yield in Biochar was 103.75 wt. %, obtained at 1.6 minutes, a ratio of 9:16 and power of 382 W. Thermogravimetric analysis showed the decomposition of hemicellulose at 300 °C, cellulose at 350 °C and lignin from 400 ° C. The greatest effect on the yield in bio-oil from POEFB, was time factor; meanwhile, for the yield in Biochar, the time and absorbent/biomass ratio had the greatest influence.